Faculty Development in Public Health: Analysis of an Experience to Strengthen Educational Quality - Cruz Gama, Esteban de Jesús; Gómez Quiroz, Jacobo; Nava Amaya, Maria Minerva; Pelcastre Villafuerte, Blanca Estela (Spanish Journal of Medical Education, 2025)
Public health faces challenges due to demographic and epidemiological transitions and the emergence of new infectious risks. Faculty training must be strengthened to develop competencies that positively impact the training of professionals capable of responding to these issues. The School of Public Health of Mexico implemented a pilot teacher training project with the objective of strengthening teaching competencies and the quality of teaching units for the Master’s in Public Health program. Objective: This study analyzes the implementation and results of this project through an educational evaluation model. Methods: A predominantly qualitative, multi-method design was carried out, divided into three stages: diagnosis, intervention (piloting), and evaluation. The main analysis focused on semi-structured interviews. In addition, a checklist was used to evaluate the teaching units before and after the intervention; a Student t-test was applied to identify significant changes. Results: The qualitative analysis showed progress in teaching planning and the use of active methodologies by faculty members. Furthermore, a significant improvement in the quality of the teaching units was identified (p-value <0.05), as a result of the complementary quantitative analysis. However, the use of technology in the classroom needs to be strengthened. Conclusion: The pilot project proved to be an effective initiative for strengthening public health teaching from a didactic and collaborative approach. It is recommended that teacher support schemes be established and the project’s sustainability ensured through academic policies.